Measuring Instant Light-Response Curve of Chlorophyll Fluorescence in Sago Palm (Metroxylon sagu Rottb.) Leaves: Different Time Measurements on Dark and Light-Adapted Leaf - Koki Asano; Hiroshi Ehara; Aidil Azhar (PLANTA TROPIKA, 2023)
This study aimed to determine the appropriate time for the chlorophyll fluorescence light curve measurement in sago palms and to avoid high values variations. The photosynthetic status of three-year-old sago palm seedlings was evaluated through the chlorophyll fluorescence measurement. The chlorophyll fluorescence light curve of measurement was evaluated under different daytime measurements. Observations on DFm/Fm’ and ETR vs. irradiances were conducted on sago palm leaves in the morning, midday, and afternoon with light and dark adaptation. The highest ETRmax value was found under a light-adapted leaf; however, the Eopt value could not be obtained. Morning time measurement on the dark-adapted leaf is the most appropriate method and time to get an Eopt value with high ETRmax.